2020
DOI: 10.1021/acsestengg.0c00064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Temperature Range for Biological Activity in Landfills Experiencing Elevated Temperatures

Abstract: There have been reports of municipal solid waste landfills with waste and gas wellhead temperatures of at least 80−100 °C, which is in excess of temperatures reported at typical landfills. Landfills experiencing heat accumulation over a broad area present a number of challenges involving leachate and gas quality and quantity, and the associated collection infrastructure. The objectives of this research were to evaluate the impact of temperature on methanogenesis and fermentation in landfills, and to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Much attention has recently been devoted to Elevated Temperature Landfills (ETLFs), in which sub-surface temperatures rise beyond normal range due to biological and chemical reactions among waste products and the trapping of heat by liquids [14,15]. While this may suppress the methane content of landfill gas by exceeding the optimal range of temperatures for methane generation [16], physical deterioration of the gas collection system due to elevated temperatures may lead to fugitive emissions of methane.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has recently been devoted to Elevated Temperature Landfills (ETLFs), in which sub-surface temperatures rise beyond normal range due to biological and chemical reactions among waste products and the trapping of heat by liquids [14,15]. While this may suppress the methane content of landfill gas by exceeding the optimal range of temperatures for methane generation [16], physical deterioration of the gas collection system due to elevated temperatures may lead to fugitive emissions of methane.…”
Section: Introductionmentioning
confidence: 99%
“…From 2012 to 2016, temperatures on both the northern and southern parts of the slices (Figure 4a) increased. An elevated temperature zone (ETZ) was defined as a waste temperature >70 °C based on Schupp et al 31 who showed that methane yields were reduced by 75% at 67.5 °C and by ∼90% at 72.5 °C in refuse samples excavated from a landfill that was exhibiting elevated temperatures. An ETZ formed in the southern part of the landfill, where the maximum temperature is predicted to reach 100 °C (Figure 4b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results show that the CH 4 /CO 2 ratios start from 0.06, 0.2 and 0.5 for each test, respectively, and then approach the stable range after around 40, 7 and 7 days, respectively. Temperatures higher than the optimum temperature, up to 55°C and 57.5°C, according to Benson (2017) and Schupp et al (2021), respectively, have been shown to reduce the primary gas ratio due to methanogenic microbial community diminishing. Based on the primary gas ratio, it can be concluded that all three sets of tests were under stable methanogenic conditions, with the only difference being the onset time and rate of reaching stable methane production.…”
Section: Biological Response Resultsmentioning
confidence: 99%